Functional Hybrid Nanoemulsions for Sumatriptan Intranasal Delivery - Ribeiro, Lígia N. M.; Rodrigues da Silva, Gustavo H.; Couto, Verônica M.; Castro, Simone R.; Breitkreitz, Márcia C.; Martinez, Carolina S.; Igartúa, Daniela E.; Prieto, Maria J.; de Paula, Eneida (Frontiers in Chemistry, 2020)
In recent years, advanced nanohybrid materials processed as pharmaceuticals have proved to be very advantageous. Triptans, such as the commercially available intranasal sumatriptan (SMT), are drugs employed in the treatment of painful migraine symptoms. However, SMT effectiveness by the intranasal route is limited by its high hydrophilicity and poor mucoadhesion. Therefore, we designed hybrid nanoemulsions (NE) composed of copaiba oil as the organic component plus biopolymers (xanthan, pectin, alginate) solubilized in the continuous aqueous phase, aiming at the intranasal release of SMT (2% w/v). Firstly, drug-biopolymer complexes were optimized in order to decrease the hydrophilicity of SMT. The resultant complexes were further encapsulated in copaiba oil-based nanoparticles, forming NE formulations. Characterization by FTIR-ATR, DSC, and TEM techniques exposed details of the molecular arrangement of the hybrid systems. Long-term stability of the hybrid NE at 25°C was confirmed over a year, regarding size (~ 120 nm), polydispersity (~ 0.2), zeta potential (~ −25 mV), and nanoparticle concentration (~ 2.1014 particles/mL). SMT encapsulation efficiency in the formulations ranged between 41–69%, extending the in vitro release time of SMT from 5 h (free drug) to more than 24 h. The alginate-based NE was selected as the most desirable system and its in vivo nanotoxicity was evaluated in a zebrafish model. Hybrid NE treatment did not affect spontaneous movement or induce morphological changes in zebrafish larvae, and there was no evidence of mortality or cardiotoxicity after 48 h of treatment. With these results, we propose alginate-based nanoemulsions as a potential treatment for migraine pain.